2020
DOI: 10.3389/fvets.2020.00090
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Reduction in Tylosin on the Prevalence of Liver Abscesses and Antimicrobial Resistance in Enterococci in Feedlot Cattle

Abstract: Recent concerns over linkages between antimicrobial resistance in human pathogens and antimicrobial use in livestock have prompted researchers to investigate management strategies that reduce the current reliance on in-feed tylosin to control liver abscesses in feedlot cattle. A total of 7,576 crossbred yearlings were allocated to the study (∼253 animals/pen, 10 replicate pens per treatment) and individually randomized to one of three treatments. Tylosin phosphate (11 ppm) was included in-feed (1) for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Those findings suggest that, in feedlot cattle, the greatest risk for liver abscess formation is during the early part of the feeding period. n In another study, 47 feedlot cattle that were fed tylosin phosphate for the first 125 DOF (first 78% of the feeding period) and between 41 and 161 DOF (last 75% of the feeding period) had more severe (A+) liver abscesses than did cattle that were fed tylosin phosphate continuously during feeding period.…”
Section: Discussionmentioning
confidence: 97%
“…Those findings suggest that, in feedlot cattle, the greatest risk for liver abscess formation is during the early part of the feeding period. n In another study, 47 feedlot cattle that were fed tylosin phosphate for the first 125 DOF (first 78% of the feeding period) and between 41 and 161 DOF (last 75% of the feeding period) had more severe (A+) liver abscesses than did cattle that were fed tylosin phosphate continuously during feeding period.…”
Section: Discussionmentioning
confidence: 97%
“…or macrolide resistance (Beukers et al, 2015;Müller et al, 2018;Davedow et al, 2020). Therefore, further field trials must examine the effect of standard feedlot diet changes in addition to the effect of TYL to improve our understanding of the interaction between diet and TYL effects.…”
Section: Figmentioning
confidence: 99%
“…(Lebreton et al, 2014;Cho et al, 2020;Agga et al, 2022a;Kaiser et al, 2022) Furthermore, enterococci have been reported from retail beef (Tyson et al, 2018), retail veal meat (Tate et al, 2021), and ground beef (Vikram et al, 2018;Schmidt et al, 2021) suggesting their foodborne implications. Antimicrobial resistance of enterococci have been extensively studied in feedlot cattle (Vikram et al, 2017;Davedow et al, 2020;Murray et al, 2022), dairy cows (Shipp and Dickson, 2012;Abdelfattah et al, 2021), and to a lesser extent in cull cows. (Pandit et al, 2021) However, such studies are rare in beef cow-calf (Agga et al, 2016) and backgrounding operations (Agga et al, 2019).…”
Section: Introductionmentioning
confidence: 99%